Protective Effect of Red Dragon Fruit (Hylocereus polyrhizus) Juice on Myocardium Structure of Albino Rat Treated by Used Cooking Oil - Novi Febrianti Febrianti; Tamara Ismi Claudya (Indonesian Journal of Biology Education, 2019)
Used cooking oil contains free radicals that are carcinogenic. These radicals able to damage the myocardium structure. Red dragon fruit has many types of antioxidants. The objective of this study was to analyze the effect of red dragon fruit juice on the histopathological image of albino rat (Rattus norvegicus) myocardium treated with used cooking oil. This study used thirty male albino rat  divided into 6 groups namely control healthy group (K), used cooking oil group (K-), vitamin C group (K+), 2.5 g red dragon fruit juice /kg body weight  (P1), 5g red dragon fruit juice/kg body weight  (P2), and 10g red dragon fruit juice 10g/ kg body weight (P3). Each group (except K) were given 2.5ml used cooking oil after one hour treated with a various dosage of red dragon juice for 30 days. On the 31st day, a surgical action was performed and the heart stained by Haematoxylin-eosin (HE). The quantitative data of parenchymal degeneration, hydropic degeneration, and myocardium necrosis were analyzed by One-Way ANOVA and LSD.The results showed that red dragon fruit juice can reduce parenchymal degeneration, hydropic degeneration, and necrosis due to the used cooking oil treatment. The most effective dose of red dragon fruit juice that reduce myocardium damage was 10 g/ kg body weight.